A Crosswalk Between UCLA and Lower Extremity Activity Scales. Issue 2 (February 2017) - Ghomrawi, Hassan M. K.; Lee, Yuo‐yu; Herrero, Christina; Joseph, Amethia; Padgett, Douglas; Westrich, Geoffrey; Parks, Michael; Lyman, Stephen
Abstract: Background: The University of California, Los Angeles (UCLA) activity scale and the Lower Extremity Activity Scale (LEAS) are the two most‐widely used and rigorously developed scales for assessing activity level in patients having joint replacement. However, the two scales are not convertible, and the level of correlation between the two is not clear. Creating a crosswalk between these scales; that is, a concordance table to convert scores from one scale to the other and vice versa, will help compare results from existing studies using either scale, and pool those results for meta‐analyses. It also will facilitate pooling data from multiple registries and data sources. Questions/Purpose: To create a crosswalk between the UCLA and the LEAS activity scales for patients having THA or TKA. Methods: Preoperative and 2‐year postoperative UCLA and LEAS scores for a cohort of patients undergoing primary TKA or THA at the Hospital for Special Surgery between May 2007 and December 2011 were matched from two registries. The scales were self‐administered by patients. Three hundred sixty‐four patients having TKAs (67% women; mean age, 67 years) and 403 having THA (66% women; mean age, 66 years) had both scores available. The equipercentile equating method was used to create the crosswalk. The standard response mean was used to assess responsiveness of the converted versus actual UCLA and LEAS scores from baseline to 2 years. Crosswalk validation also included comparing the area under the receiver operating characteristic curve of the actual and converted scores to evaluate their ability to discriminate different levels of function measured using the Hip dysfunction and Osteoarthritis Outcome Score activities of daily living subscale for patients having THA and the Knee injury and Osteoarthritis Outcome Score activities of daily living subscale for patients having TKA. Difference between scores was assessed using the inequality test. Results: For patients having TKA, converted mean scores (UCLA to LEAS, 9.5 ± 3.0; LEAS to UCLA, 4.7 ± 2.1) were not different from the actual scores (UCLA, 4.8 ± 2.1; LEAS, 9.4 ± 2.9). Standard response means for the converted scores (UCLA to LEAS, 0.47; LEAS to UCLA, 0.52) were not different from those of the actual scores (UCLA, 0.48; LEAS, 0.56). The areas under the receiver operating characteristic curve also were not different for actual and converted scores for THA and TKA. Conclusion: We have developed and validated a crosswalk to easily convert UCLA to LEAS scores (and vice versa) for THA and TKA. Reproducing the crosswalk for other lower extremity conditions or surgical procedures may extend its utility to studies assessing activity in patients having these conditions or procedures.